Modulated internal electric field, dielectric susceptibility and polarization in ferroelectric superlattices - Chew, Khian Hooi; Iwata, M.; Lim, K.G.; Ong, L.H. (2013)
A thermodynamic model for describing interface intermixing in a superlattice combining a ferroelectric and a paraelectric is developed. Formation of intermixed layer at interfaces leads to a periodic modulation of ferroelectric properties in these superlattices. Spatially-varying internal electric field, dielectric susceptibility and polarization of these superlattices are calculated. Effects of modulation period and temperature on the internal electric field, dielectric susceptibility and polarization of these superlattices with inhomogeneous properties are examined. Correlation between these ferroelectric properties is established and discussed. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.